Studies of some poly (phenylene vinylene) derivatives and their composites : synthesis and characterization - Wang, Yu Ming. (2008)
This thesis describes the study of some new poly(phenylene vinylene) (PPV) derivatives and their crosslinked rubber-silica composites. Chapter 1 gives a literature review of PPV derivatives and their electrical-optical properties. Chapter 2 describes the synthesis of some new PPV derivatives and their photoluminescent (PL) and excellent electroluminescent (EL) properties. l,4-Di-a-bromomethyl-2,3,5,6- tetrafluorobenzene has been successfully synthesized. The compound has a melting point of 126 °C and the structure is carefully characterized by ]H NMR, GC/MS, HPLC and X-ray diffraction methods. The compound is used as the monomer for the preparation of poly(2,3,5,6-/e/ra-fluoro-phenylene vinylene) (PTFPV) through the chlorine precursor route (CPR). The conjugated polymer shows good PL and EL properties. Another new PPV derivative, poly(2,3,5,6-tetrabromo-l,4-phenylene vinylene) (PTBrPV) has also been synthesized. However, the polymer has very poor PL properties. Poly(2,5-dimethoxy-l,4-phenylene vinylene) (PDMoPV) are prepared via both the CPR and Wessling methods. The PDMoPV prepared via Wessling method fluoresces at a longer wavelength with the maximum at 540 nm, while the fluorescence of the PDMoPV via CPR has blue shifted with the maximum at 505 nm. P(TFPV-co-DMoPV) copolymers are also successfully obtained. Single layer LEDs have been fabricated using the polymers prepared. The ITO/PTFPV/A1, ITO/PDMoPV (via Wessling methodVAl, ITO/PDMoPV (via CPRVA1 and ITO/P(TFPV-co-DMoPV)/Al devices are found to emit blue-green light at very low turn-on voltages of 4, 7, 4 and 8 V respectively.